Overseas experience in horticulture â€“ a way forward - Dutt, Som (Indian Horticulture, 2019)
â€œSenior Executive Development Programme for Senior Officers on Developing Effective Organizational Leadership for Senior Officers of ICARâ€, was organized by ASCI (Administrative Staff College of India), Hyderabad. As a part of International component, Dr T. Janakiram visited South-East Asian countries: China, Malaysia and Thailand during 15-24 April 2018, with the objectives to visit various research institutions, production units, processing facilities and other government departments for gaining insights on good practices in agriculture and allied disciplines in China, Malaysia and Thailand. The Editor (Indian Horticulture), interacted with Dr T. Janakiram, ADG (Hort. Sci.). The excerpts are furnished herewith.